Differentiated Meta-PSO Methods for Array Optimization - Selleri, S.; Mussetta, M.; Pirinoli, P.; Zich, R.E.; Matekovits, L. (IEEE transactions on antennas and propagation, 2008)
The particle swarm optimization (PSO) method has been successfully applied to different electromagnetic optimization problems. Because of the complexity of this kind of problems, the associated cost function is in general computationally expensive. A fast convergence of the optimization algorithm is hence required to attain results in short time. Here few variations over the standard algorithm, referred to as differentiated meta-PSO, aimed to enhance the global search capability, and to improve the algorithm convergence, are introduced. In order to verify their effectiveness the different techniques have been first applied to benchmark test functions and then used for the optimization of a planar array.